Effects of COVID-19 pandemic on mental health among frontline healthcare workers: A systematic review and meta-analysis - Tong, Jie; Zhang, Jie; Zhu, Na; Pei, Yu; Liu, Weiqing; Yu, Wei; Hu, Chengping; Sun, Xirong (Frontiers in Psychology, 2023)
Background As some countries announced to remove Coronavirus Disease 2019 (COVID-19) border, it indicates that the COVID-19 may have entered its terminal stage. In this COVID-19 pandemic, the mental health of frontline healthcare workers (HCWs) experienced unprecedented challenges. However, the impact of the COVID-19 pandemic on mental health among frontline HCWs lacks a high-quality and long-term systematic review and meta-analysis. Methods We conducted a systematic review and meta-analysis according to PRISMA guidelines. The system searches EMBASE, MEDLINE, PsycINFO, Cochrane Library, ScienceNet, and ERIC. Analyze the mental health problems of frontline HCWs in different regions and periods, including insomnia, stress, anxiety and depression. This study was registered in PROSPERO under the number CRD42021253821. Results A total of 19 studies on the effects of COVID-19 pandemic on mental health among frontline HCWs were included in this study. The overall prevalence of insomnia was 42.9% (95% CI, 33.9–51.9%, I2 = 99.0%) extracted from data from 14 cross-sectional studies (n = 10 127), 1 cohort study (n = 4,804), and 1 randomized controlled trial (RCT; n = 482) in 10 countries. The overall prevalence of stress was 53.0% (95% CI, 41.1–64.9%, I2 = 78.3%) extracted from data from nine cross-sectional studies (n = 5,494) and 1 RCT study (n = 482) from eight countries. The overall prevalence of anxiety and depression was 43.0% (95% CI, 33.8–52.3%, I2 = 99.0%) and 44.6% (95% CI, 36.1–53.1%, I2 = 99.0%) extracted from data from 17 cross-sectional studies (n = 11,727), one cohort study (n = 4,804), and one RCT study (n = 482) from 12 countries. The prevalence of stress and depression was higher in 2020, while the prevalence of insomnia and anxiety was higher in 2021. The prevalence of mental health problems among physicians was higher than that of other frontline HCWs. The prevalence of mental health problems among frontline HCWs is higher in South America and lower in North America. Conclusions This systematic review and meta-analysis showed that the COVID-19 pandemic have significant effects on mental health among frontline HCWs. The overall prevalence of insomnia, stress, anxiety and depression among frontline HCWs is high. Therefore, the health policy-makers should pay attention to and respond to the mental health problems of frontline HCWs in the context of public health emergencies. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/.